Multimaterial Microfluidic 3D Printing of Textured Composites with Liquid Inclusions - Li, Xiying (Adv Sci (Weinh), 2018)
3D printing with a high degree of spatial and compositional precision could open new avenues to the design and fabrication of functional composites. By combining the direct ink writing and microfluidics, a multimaterial 3D printing system for fabricating textured composites with liquid inclusions of programmable spatial distribution and compositions is reported here. Phase diagrams for the rational selection of desired printing parameters are determined through a combination of simple theoretical analysis and experimental studies. 1D, 2D, and 3D structures programmed with desired inclusion patterns and compositions are fabricated. Moreover, the versatility of this 3D printing framework in fabricating layered composite beams of tunable thermal property and self‐healing materials is demonstrated. The proposed multimaterial microfluidic 3D printing framework could be broadly applicable for structural composites and soft robotic devices.